Telenursing manual for providing care to patients using clean intermittent urinary catheterization - Valtuir Duarte de Souza-Junior; Isabel Amélia Costa Mendes; Alessandra Mazzo; Cristiano Alves dos Santos; Elaine Maria Leite Rangel Andrade; Simone de Godoy (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objective: To develop and evaluate apparent and content validity of a telenursing manual to support nurses in the care delivery of patients using clean intermittent urinary catheterization. Methods: Methodological study addressing the development and validation of a telenursing manual. The expert group who validated the telenursing manual was composed of 11 nurses. An inter-rater level of agreement of 70% was considered for each aspect of the instrument. Results: The following levels of agreement were obtained for each aspect: Language 97%, Content 97.7% and Objectives, Relevance, Functionality and Usability 100% each. Conclusion: The manual is available for access and represents an important initiative for the field of telenursing in Brazil, assisting nurses in the telecare provided to patients using clean intermittent urinary catheterization.